2001
DOI: 10.1002/1097-0274(200102)39:2<194::aid-ajim1006>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Job strain and sickness absence among nurses in the province of Qu�bec

Abstract: Background Using Karasek's job strain model, the objective of the study was to determine whether nurses exposed to job strain had a higher incidence of sick leave than nurses not exposed. Methods The design was longitudinal. Data on sick leave were collected for 1,793 nurses for a 20‐month period: short‐term leaves and certified sick leaves. The Job Content Questionnaire was used to measure psychological demands, job decision latitude, and social support at work. Results Short‐term sick leaves were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 28 publications
6
116
0
6
Order By: Relevance
“…Job strain as a predictor of sickness absence in women is in line with findings from longitudinal studies in nurses (13,53); and another longitudinal study covering a broader range of workers found that the strongest mediator in the association between gender and sickness absence was job strain (54). Also, a recent longitudinal population-based study on both men and women found support for the association between job strain and longterm sickness absence (12).…”
Section: Discussionsupporting
confidence: 69%
“…Job strain as a predictor of sickness absence in women is in line with findings from longitudinal studies in nurses (13,53); and another longitudinal study covering a broader range of workers found that the strongest mediator in the association between gender and sickness absence was job strain (54). Also, a recent longitudinal population-based study on both men and women found support for the association between job strain and longterm sickness absence (12).…”
Section: Discussionsupporting
confidence: 69%
“…These include gender distribution, hierarchy, and a high load of both physical and emotional stress. 3,6,14,21,22,24,25 Studies investigating the characteristics related to sickness among these professionals are rare in Brazil. There is not enough adequate research in this field, the profile of morbidities associated with work absenteeism among nursing professionals being hardly known.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies looked at interview-based psychiatric disorders (Kessler and Frank 1997;Dewa and Lin 2000;Kouzis and Eaton 1994;Suija et al 2009;Kruijshaar et al 2003;Broadhead et al 1990;Jenkins 1985;Laitinen-Krispijn and Bijl 2000), others at questionnaire-based psychological symptoms (Hilton et al 2008;Bültmann et al 2005Bültmann et al , 2006Virtanen et al 2007;Kivimäki et al 2001;Bourbonnais and Mondor 2001;Andrea et al 2003;Väänänen et al 2003; Lexis et al 2009;Duijts et al 2006;Eriksen et al 2003;Janssen et al 2003;Ahola et al 2008;Borritz et al 2006;Kivimäki et al 2007;Krantz and Ostergren 2002). The symptom predictors studied were distress (Hilton et al 2008;Bültmann et al 2005;Virtanen et al 2007;Kivimäki et al 2001;Bourbonnais and Mondor 2001;Andrea et al 2003;Väänänen et al 2003), depression (Bültmann et al 2006; Lexis et al 2009;Duijts et al 2006;Eriksen et al 2003), fatigue (Bültmann et al 2005;Andrea et al 2003;Duijts et al 2006;Eriksen et al 2003;…”
mentioning
confidence: 99%
“…Few studies analyzed SA both in terms of frequency and duration as recommended by Hensing et al (1998). SA was either established by self-report (Hilton et al 2008;Kessler and Frank 1997;Dewa and Lin 2000;Kouzis and Eaton 1994;Suija et al 2009;Kruijshaar et al 2003;Broadhead et al 1990;Jenkins 1985;Laitinen-Krispijn and Bijl 2000;Eriksen et al 2003;Borritz et al 2006) or by organizational absence records (Bültmann et al 2005(Bültmann et al , 2006Virtanen et al 2007;Kivimäki et al 2001Kivimäki et al , 2007Bourbonnais and Mondor 2001;Andrea et al 2003;Väänänen et al 2003;Lexis et al 2009;Duijts et al 2006;Janssen et al 2003;Ahola et al 2008;Krantz and Ostergren 2002). Not all studies have taken into account possible confounding or effect modification by other factors.…”
mentioning
confidence: 99%